Copper alloy for high-strength and high-corrosion-resistance propeller and preparation method of copper alloy
By introducing specific elements and process treatments into aluminum bronze, a high-strength, high corrosion resistance copper alloy is formed, which solves the problem of insufficient performance of existing aluminum bronze under high-speed impact and strong current corrosion, and achieves significant improvement in strength and corrosion resistance.
Patent Information
- Application Number
- CN202510108676.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-25
AI Technical Summary
The existing aluminum bronze propellers cannot meet the strict requirements of high-speed power systems for material service performance under high-speed impact and strong current corrosion, especially in terms of corrosion resistance and mechanical properties.
A high-strength and high corrosion resistance copper alloy is adopted, including Al 9.0% to 13.0%, Ni 4.0% to 6.0%, Fe 4.0% to 6.0%, Mn 1.5% to 2.5% and Y 0.05% to 0.15%. Through vacuum induction furnace melting and annealing treatment, combined with laser energy input, a single martensite slat structure is formed to improve surface hardness and corrosion resistance.
Compared with the existing 9-4-4 series aluminum bronze, the strength of copper alloy is 60%, corrosion resistance is 2 times, and cavitation resistance is about 4 times, meeting the strict requirements of high-speed power systems for material service performance.
Smart Images

Figure CN119876685A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of copper alloys, and in particular to a high-strength and high-corrosion-resistant copper alloy for propellers and a preparation method thereof. Background Art
[0002] At present, the global shipbuilding, ocean, and marine engineering manufacturing fields have increasingly stringent requirements on the service environment and performance of military components. The output power of power propulsion devices under extreme service conditions has been increased to more than 5,000 kilowatts. The largest aluminum-bronze propeller currently manufactured in China has reached 12.5 meters. Therefore, more stringent requirements are also put forward for the service performance of materials in high-speed power systems, but the service performance and time of existing aluminum-bronze cannot meet the high-speed impact and strong current corrosion of alternating loads. The corrosion resistance and mechanical performance upper limit of aluminum-bronze propellers restrict the comprehensive and rapid advancement of my country's marine engineering construction. Summary of the invention
[0003] Based on this, the present invention provides a high-strength and high-corrosion-resistant copper alloy for propellers and a preparation method thereof. The present invention improves the strength and corrosion resistance of aluminum bronze, and the strength is increased by 60% compared with the existing 9-4-4 series aluminum bronze, the corrosion resistance is increased by 2 times, and the cavitation resistance is increased by about 4 times.
[0004] The high-strength and high-corrosion-resistant copper alloy for propellers of the present invention comprises the following elements in percentage by mass:
[0005] Al: 9.0% to 13.0%; Ni: 4.0% to 6.0%; Fe: 4.0% to 6.0%; Mn: 1.5% to 2.5%; Y: 0.05% to 0.15%, and the balance is copper and unavoidable impurities.
[0006] The method for preparing the high-strength and high-corrosion-resistant copper alloy for propellers of the present invention comprises the following steps:
[0007] (1) Ingredients: Weigh copper powder, aluminum powder, nickel powder, manganese powder, iron powder, and Cu-Y alloy according to the element content in the copper alloy and set aside;
[0008] (2) Melting: The weighed Cu-Y alloy is sealed in a pure copper tube and fixed on the mechanical arm of a vacuum induction furnace. Copper powder, aluminum powder, nickel powder, manganese powder and iron powder are added to the crucible of the vacuum induction furnace. After the vacuum induction furnace is evacuated, a protective atmosphere is introduced and heating is started. When all the solids in the crucible are melted and the temperature rises to 1500°C, the induction current is turned off, and the mechanical arm is quickly operated to immerse the pure copper tube sealing the Cu-Y alloy under the melt surface. The mechanical arm is lifted, the induction current is turned on and the temperature is kept constant for 2-5 minutes. After the temperature is kept constant, casting is performed. After the casting is completed, the ingot is obtained after cooling.
[0009] (3) Annealing treatment: placing the ingot obtained in step (2) in a muffle furnace and heating it to 900° C. to 1000° C. for 5 h to 8 h, followed by cooling in the furnace to obtain an ingot with uniform chemical composition;
[0010] (4) Surface strengthening treatment: After the ingot has been annealed in step (3), the surface is cleaned and dried, polished, and then cleaned with alcohol. After drying, the ingot is sprayed with a light-absorbing material. After being fixed, the ingot is scanned with a laser, wherein the energy density of the laser is 20 J / mm 2 ~-35J / mm 2 , power is 2.5kW~3.5kW.
[0011] Preferably, the content of Y in the Cu-Y alloy is 15wt.% to 25wt.%.
[0012] Preferably, the protective atmosphere in step (2) is argon or nitrogen.
[0013] Preferably, the heating rate in step (3) is 3°C / min to 6°C / min.
[0014] Preferably, the light-absorbing material in step (4) is the light-absorbing coating prepared in patent number CN113527963.A. The spraying thickness of the light-absorbing material is 1 to 1.5 mm.
[0015] Preferably, the laser scanning speed in step (4) is 5 to 15 mm / s.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] The present invention provides a high-strength and high-corrosion-resistant copper alloy for propellers and a preparation method thereof. The preparation method is simple to operate and low in cost. At the same time, the present invention optimizes the alloy matrix phase distribution and strength by regulating the alloy components, such as Figure 1 The XRD spectrum shown in the figure shows that when the Al content increases to 11%, diffraction peaks at 40.3° and 46.6° appear. Figure 2 The microstructure distribution in the figure shows that the β' phase appears in the alloy. The 44° diffraction peak corresponding to κ is also more obvious. Combined with the microstructure diagram, it shows that the κ phase in the alloy increases. The hard β'-Cu phase and κ phase ((Fe, Ni)Al) in the alloy increase, and the microhardness of the β'-Cu phase and κ phase are higher than that of the matrix α-Cu alloy as a whole, resulting in the increase of alloy hardness with the increase of Al content, such as Figure 3 Hardness curve shown.
[0018] The present invention combines laser energy input to obtain a single martensitic lath structure on the alloy surface, such as Figure 4As shown. By analyzing the microstructure of the martensite structure, we found that the surface layer was transformed from a complex multiphase structure to a single martensite structure. The laths were in the same direction, and nano-precipitates were dispersed between the laths. This three-level composite structure can effectively even out the surface potential difference and eliminate phase selective corrosion. The surface morphology and surface potential distribution of aluminum bronze before and after laser treatment were observed by atomic force microscopy (AFM), as shown in Figure 5 shown. Figure 5 (b, d, f) are the height differences of the sample surface. The brighter the color, the greater the height value of the area. Figure 5 (a, c, e) are the distribution of surface contact potential difference. The surface potential difference is related to the instrument probe and the surface work function of each phase. The work function is the minimum energy value required for electrons to escape from the solid surface. The lower the work function, the higher the surface contact potential difference, and the color tends to red. The α phase is harder than the κ phase, so it is easier to be removed by abrasive particles and has a smaller surface height value. The α phase has a lower potential difference than the κ phase, and the potential difference is highest at the phase interface, with a maximum value of up to 140mV. After laser energy input, the surface structure is transformed into a single martensitic lath, and the potential difference is highest at the martensitic grain boundary, reaching 80mV. Combined with Figure 6 The electrochemical corrosion morphology diagram intuitively shows that after the laser energy input, the corrosion failure of the aluminum bronze surface changes from the violent phase selection corrosion of the multiphase structure to the mild intergranular corrosion and uniform corrosion inside the lath. Figure 7-8 As shown in the figure, after laser energy input, the surface hardness of aluminum bronze increased significantly, the cavitation weight loss decreased, and the cavitation resistance was significantly improved. Fig. 9 From the cavitation cross-sectional microstructure diagram, it can be seen that the α phase of cast aluminum bronze is corroded and peeled off first in the cavitation environment, which weakens the fixation effect on the κ phase and causes the κ phase to detach, leading to the expansion of the cavitation pit, increasing the corrosion contact area, and accelerating the corrosion of the α phase; mechanical peeling and electrochemical corrosion promote each other, aggravating the cavitation failure. After laser energy input, the β' phase undergoes uniform intergranular corrosion in the medium environment, while the hardness is improved, the resistance to mechanical deformation is enhanced, and it is not easy to produce large-scale cavitation pits. The main failure form is the layer-by-layer corrosion and peeling of the β' phase.
[0019] This preparation method improves the overall strength and corrosion resistance of the alloy by regulating the distribution of the aluminum bronze matrix composition and phases, and combines laser energy input to obtain uniform structure, eliminate phase selective corrosion, and improve strength, further improving the cavitation resistance of the aluminum bronze propeller. The strengthening mechanism is as follows Fig.10 shown. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The XRD spectrum distribution of the copper alloys prepared in Examples 1 to 3 and Comparative Example 1;
[0021] Figure 2The microstructure diagrams of the copper alloys prepared in Example 1(a), Example 2(b), Example 3(c) and Comparative Example 1(d);
[0022] Figure 3 The microhardness distribution of the copper alloys prepared in Examples 1 to 3 and Comparative Example 1;
[0023] Figure 4 This is the microstructure diagram of the copper alloy surface in Example 1 after laser energy input;
[0024] Figure 5 AFM images of the copper alloy surface of Example 1 before and after laser energy input;
[0025] Figure 6 The electrochemical corrosion morphology of the copper alloy surface in Example 1 before and after laser energy input;
[0026] Figure 7 The cavitation weight loss and hardness distribution curves of the copper alloy in Example 1 before and after laser energy input;
[0027] Figure 8 The surface organization diagram of the copper alloy cavitation failure in Example 1 before and after the laser energy input;
[0028] Fig. 9 The cross-sectional microstructure diagram of the copper alloy cavitation failure in Example 1 before and after laser energy input;
[0029] Fig.10 This is the strengthening mechanism diagram of this preparation method. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and advantages of the present invention clearer, the preferred embodiments of the present invention are further described in detail in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] 5g Cu-Y alloy (Y content is 20wt.%) is sealed in a pure copper tube and fixed on the mechanical arm of a vacuum induction furnace. 790g copper powder, 90g aluminum powder, 40g nickel powder, 20g manganese powder and 40g iron powder are added to the crucible of the vacuum induction furnace. The vacuum induction furnace is evacuated to below 15Pa, and the protective atmosphere argon gas is introduced to 0.05MPa, and then the induction power supply is introduced to start heating. When all the solids in the crucible are melted and heated to 1500℃, the induction current is turned off, and the mechanical arm is quickly operated to immerse the pure copper tube of the sealed Cu-Y alloy under the melt liquid surface, the mechanical arm is lifted, the induction current is turned on and the heat is continued for 3min, and casting is performed after heat preservation. After casting is completed, it is cooled for about 30min and taken out. The obtained ingot is placed in a muffle furnace and heated to 950℃ at a heating rate of 5℃ / min for 6h and cooled with the furnace. After the ingot is cleaned, dried and sprayed with light-absorbing material, the power is 3kW and the energy density is 25J / mm 2 Laser energy is input under the condition of high temperature and low humidity to adjust the structure and obtain a copper alloy with a single and uniform structure.
[0033] The prepared copper alloy was tested, and the mass percentage of each element in the copper alloy was as follows:
[0034] Al 9.06%, Ni 4%, Fe 4%, Mn 2%, Y 0.03%, and the balance being copper and inevitable impurities.
[0035] The copper alloy prepared in Example 1 has a hardness of HV=162.37 and a corrosion current of 15.32 μA / cm 2 , cavitation 20h weight loss 46mg, strengthening layer hardness HV = 323.65, corrosion current 9.157μA / cm 2 , cavitation weight loss of 18 mg in 20 hours.
[0036] Example 2
[0037] 10g Cu-Y alloy (Y content is 20wt.%) is sealed in a pure copper tube and fixed on the mechanical arm of a vacuum induction furnace. 770g copper powder, 100g aluminum powder, 50g nickel powder, 20g manganese powder and 50g iron powder are added to the crucible of the vacuum induction furnace. The vacuum induction furnace is evacuated to below 15Pa, and the protective atmosphere argon gas is introduced to 0.05MPa, and then the induction power supply is introduced to start heating. When all the solids in the crucible are melted and heated to 1500℃, the induction current is turned off, and the mechanical arm is quickly operated to immerse the pure copper tube of the sealed Cu-Y alloy under the melt liquid surface, the mechanical arm is lifted, the induction current is turned on and the heat preservation is continued for 3min, and casting is carried out after heat preservation. After casting is completed, it is cooled for about 30min and taken out. The obtained ingot is placed in a muffle furnace and heated to 950℃ at a heating rate of 5℃ / min for 6h and cooled with the furnace. After the ingot is cleaned, dried and sprayed with light-absorbing material, the power is 3kW and the energy density is 25J / mm2 Laser energy is input under the condition of high temperature and low humidity to adjust the structure and obtain a copper alloy with a single and uniform structure.
[0038] The prepared copper alloy was tested, and the mass percentage of each element in the copper alloy was as follows:
[0039] Al 9.82%, Ni 4%, Fe 4%, Mn 1.98%, Y: 0.1%, and the balance is copper and inevitable impurities.
[0040] The copper alloy prepared in Example 2 has a hardness of HV=210.44 and a corrosion current of 15.52 μA / cm 2 , cavitation 20h weight loss 39.3mg, strengthening layer hardness HV = 302.714, corrosion current 7.98μA / cm 2 , cavitation weight loss of 19.7 mg in 20 hours.
[0041] Example 3
[0042] 20g Cu-Y alloy (Y content is 20wt.%) is sealed in a pure copper tube and fixed on the mechanical arm of a vacuum induction furnace. 750g copper powder, 130g aluminum powder, 40g nickel powder, 20g manganese powder and 40g iron powder are added to the crucible of the vacuum induction furnace. The vacuum induction furnace is evacuated to below 15Pa, and the protective atmosphere argon gas is introduced to 0.05MPa, and then the induction power supply is introduced to start heating. When all the solids in the crucible are melted and the temperature is raised to 1500℃, the induction current is turned off, and the mechanical arm is quickly operated to immerse the pure copper tube of the sealed Cu-Y alloy under the melt liquid surface, the mechanical arm is lifted, the induction current is turned on and the heat preservation is continued for 3min, and casting is carried out after heat preservation. After casting is completed, it is cooled for about 30min and taken out. The obtained ingot is placed in a muffle furnace and heated to 900℃ at a heating rate of 5℃ / min for 6h and cooled with the furnace. After the ingot is cleaned, dried and sprayed with light-absorbing material, the power is 3kW and the energy density is 25J / mm 2 Laser energy is input under the condition of high temperature and low humidity to adjust the structure and obtain a copper alloy with a single and uniform structure.
[0043] The prepared copper alloy was tested, and the mass percentage of each element in the copper alloy was as follows:
[0044] Al 13%, Ni 4.1%, Fe 4.0%, Mn 1.98%, Y: 0.3%, and the balance is copper and inevitable impurities.
[0045] The copper alloy prepared in Example 3 has a hardness of HV=280.62 and a corrosion current of 12.864 μA / cm 2 , cavitation 20h weight loss 15.8mg, strengthening layer hardness HV = 343.68, corrosion current 5.5389μA / cm 2, cavitation weight loss of 11.2 mg in 20 hours.
[0046] Comparative Example 1
[0047] 810g copper powder, 90g aluminum powder, 40g nickel powder, 20g manganese powder and 40g iron powder are added to the crucible of the vacuum induction furnace. The vacuum induction furnace is evacuated to below 15Pa, and the protective atmosphere argon gas is introduced to 0.05MPa, and then the induction power supply is introduced to start heating. When all the solids in the crucible are melted and the temperature is raised to 1450℃, it is kept warm for 10min, and then cast after heat preservation. After casting, it is cooled for about 30min and taken out. The obtained ingot is placed in a muffle furnace and heated to 900℃ at a heating rate of 5℃ / min, kept warm for 6h and cooled with the furnace to obtain a copper alloy.
[0048] The prepared copper alloy was tested, and the mass percentage of each element in the copper alloy was as follows:
[0049] Al 9.01%; Ni 4%; Fe 3.98%; Mn 1.96%; the balance is copper and inevitable impurities.
[0050] The copper alloy prepared in Comparative Example 1 has a hardness of HV=149.45 and a corrosion current of 26.7 μA / cm 2 , cavitation weight loss of 54.1 mg in 20 hours.
[0051] from Figure 1 It can be seen that the room temperature equilibrium structure of the alloy is composed of α-Cu, β-Cu, and κ phases. As the Al content increases, the β-Cu diffraction peak becomes more prominent. Figure 2 It can be seen that when the Al content is less than 10%, the room temperature equilibrium structure of the alloy consists of α-Cu, β-Cu and different forms of κ phase. Figure 2 As shown in (ab, d), when the Al content is 13%, the room temperature structure of the alloy consists of spherical κ phase and Cu matrix phase. Figure 2 (c) as shown.
[0052] from Figure 3 It can be seen that the microhardness of the alloy in the cast state increases with the increase of Al content.
[0053] from Figure 4 It can be seen that after laser treatment, a single uniform martensitic fine-grained structure is formed on the alloy surface, and the original α-Cu phase in the strengthening layer is transformed into an equiaxed crystal as shown in Figure ①. The interior of the equiaxed crystal is composed of lath bundles with different orientations, and nano-scale particles are distributed inside the lath bundles, as shown in the transmission images of Figures ②-④.
[0054] from Figure 5 It can be seen that Figure 5 (a,c) and Figure 5(e) Surface morphology distribution of aluminum bronze after casting and laser treatment, κ Ⅱ Phase and κ Ⅲ Compared with the α phase, it is harder and more wear-resistant, so it has a higher height. After laser treatment, the alloy surface is a uniform martensitic lath structure with uniform hardness distribution. Figure 5 (b, d) and Figure 5 (f) Surface potential distribution of aluminum bronze after casting and laser treatment, κ Ⅱ Phase and κ Ⅲ Compared with the α phase, the surface contact potential is higher, and the potential difference is the largest at the boundary between the two phases. After laser treatment, the surface potential difference is more evenly distributed, mainly at the grain boundary and the intracrystalline potential difference.
[0055] from Figure 6 It can be seen that Figure 6 (a,c) and Figure 6 (b, d) are the electrochemical corrosion morphologies of aluminum bronze before and after laser treatment, respectively. The surface corrosion of the cast aluminum bronze is more serious, and obvious phase-selective corrosion occurs. The α phase near the κ phase corrodes and falls off preferentially, causing the κ phase to be more three-dimensionally prominent. After laser treatment, the corrosion mechanism is mainly intergranular corrosion of martensitic laths, the corrosion surface roughness is lower, and the corrosion reaction is milder.
[0056] from Figure 7 It can be seen that the cavitation weight loss of aluminum bronze after laser treatment is significantly reduced, and the cavitation resistance and hardness are significantly improved.
[0057] from Figure 8 It can be seen that Figure 8 (a,b) and Figure 8 (c, d) are the cavitation surface morphologies of the as-cast and laser-treated aluminum-bronze alloys, respectively. The as-cast surface is severely corroded and has a large number of holes. The κ phase protrudes after the α phase corrodes and falls off preferentially. The cavitation surface roughness of the alloy after laser treatment is smaller, a small amount of tissue corrosion and peeling occurs, and the martensite lath grain boundaries are more obvious.
[0058] from Fig. 9 It can be seen that Fig. 9 (a,b) and Fig. 9 (c, d) are the cross-sectional morphologies of the cast and laser-treated aluminum bronze alloys. During the cavitation process, the α phase with lower hardness undergoes plastic deformation under mechanical impact, which accelerates corrosion and spalling under the action of electrochemical corrosion, leaving vacancies to increase the corrosion area and stress concentration points. The cracks extend along the phase interface to further accelerate cavitation failure. The cross-section after laser treatment shows plastic deformation. After magnification, it is found that the surface martensite laths are corroded and peeled off between grains, and there is no severe internal crack extension.
[0059] from Fig.10It can be seen that the present invention summarizes the strengthening mechanism of the example, improves the phase composition ratio of the cast alloy through component design to increase the strength and corrosion resistance of the alloy, and prepares a single uniform martensitic strengthening layer through collaborative laser processing, further improving the alloy's cavitation resistance.
[0060] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A high-strength and high-corrosion-resistant copper alloy for propellers, characterized in that: The following elements are included in mass percentage: Al: 9.0% ~ 13.0%; Ni: 4.0% ~ 6.0%; Fe: 4.0% ~ 6.0%; Mn: 1.5% ~ 2.5%; Y: 0.05% to 0.15%, the remainder being copper and inevitable impurities.
2. The method for preparing the high-strength and high-corrosion-resistant copper alloy for propellers according to claim 1, characterized in that: The following steps are involved: (1) Ingredients: Weigh copper powder, aluminum powder, nickel powder, manganese powder, iron powder, and Cu-Y alloy according to the element content in the copper alloy and set aside; (2) Melting: The weighed Cu-Y alloy is sealed in a pure copper tube and fixed on the mechanical arm of a vacuum induction furnace. Copper powder, aluminum powder, nickel powder, manganese powder and iron powder are added to the crucible of the vacuum induction furnace. After the vacuum induction furnace is evacuated, a protective atmosphere is introduced and heating is started. When all the solids in the crucible are melted and the temperature rises to 1500°C, the induction current is turned off, and the mechanical arm is quickly operated to immerse the pure copper tube sealing the Cu-Y alloy under the melt surface. The mechanical arm is lifted, the induction current is turned on and the temperature is kept constant for 2-5 minutes. After the temperature is kept constant, casting is performed. After the casting is completed, the ingot is obtained after cooling. (3) Annealing treatment: placing the ingot obtained in step (2) in a muffle furnace and heating it to 900° C. to 1000° C. for 5 h to 8 h, followed by cooling in the furnace to obtain an ingot with uniform chemical composition; (4) Surface strengthening treatment: After the ingot has been annealed in step (3), the surface is cleaned and dried, polished, and then cleaned with alcohol. After drying, the ingot is sprayed with a light-absorbing material. After being fixed, the ingot is scanned with a laser, wherein the energy density of the laser is 20 J / mm 2 ~-35J / mm 2 , power is 2.5kW~3.5kW.
3. The preparation method according to claim 2, characterized in that: The content of Y in the Cu-Y alloy is 15wt.% to 25wt.%.
4. The preparation method according to claim 2, characterized in that: The protective atmosphere in step (2) is argon or nitrogen.
5. The preparation method according to claim 2, characterized in that: The heating rate in step (3) is 3°C / min to 6°C / min.
6. The preparation method according to claim 2, characterized in that: The spraying thickness of the light absorbing material in step (4) is 1 to 1.5 mm.
7. The preparation method according to claim 2, characterized in that: The laser scanning speed in step (4) is 8 to 15 mm / s.
Citation Information
Patent Citations
Copper-aluminum-iron-nickel-manganese alloy capable of improving mechanical properties
CN105088003A
Wear-resistant corrosion-resistant multi-element manganese-aluminum bronze brazing alloy and preparation method thereof
CN111074089A
Heat treatment process method for improving strength and toughness of nickel-aluminum bronze alloy
CN115044747A
Cavitation-erosion-resistant copper alloy surface structure and preparation method thereof
CN116497301A
Cast copper alloy for producing sea water pump valve and its preparing method
CN1492064A